Clinical Significance of Isolated Atypical Transient Symptoms in a Cohort With Transient Ischemic Attack. Issue 6 (June 2017) - Lavallée, Philippa C.; Sissani, Leila; Labreuche, Julien; Meseguer, Elena; Cabrejo, Lucie; Guidoux, Céline; Klein, Isabelle F.; Touboul, Pierre-Jean; Amarenco, Pierre
Abstract : Background and Purpose—: Contrary to typical transient symptoms (TS), atypical TS, such as partial sensory deficit, dysarthria, vertigo/unsteadiness, unusual cortical visual deficit, and diplopia, are not usually classified as symptoms of transient ischemic attack when they occur in isolation, and their clinical relevance is frequently denied. Methods—: Consecutive patients with recent TS admitted in our transient ischemic attack clinic (2003–2008) had systematic brain, arterial, and cardiac investigations. We compared the prevalence of recent infarction on brain imaging, major investigational findings (symptomatic intracranial or extracranial atherosclerotic stenosis ≥50%, cervical arterial dissection, and major source of cardiac embolism), and 1-year risk of major vascular events in patients with isolated typical or atypical TS and nonisolated TS, after exclusion of the main differential diagnoses. Results—: Among 1850 patients with possible or definite ischemic diagnoses, 798 (43.1%) had isolated TS: 621 (33.6%) typical and 177 (9.6%) atypical. Acute infarction on brain imaging was similar in patients with isolated atypical and typical TS but less frequent than in patients with nonisolated TS, observed in 10.0%, 11.5%, and 15.3%, respectively ( P <0.0001). Major investigational findings were found in 18.1%, 26.4%, and 26.3%, respectively ( P =0.06). One-year risk of a major vascular events was not significantly different in the 3 groups. Conclusions—: Transient ischemic attack diagnosis should be considered and investigated in patients with isolated atypical TS. Abstract : Supplemental Digital Content is available in the text.